Cognitional Impairment: Is There a Role for Cognitive Assessment in the Treatment of Individuals Civilly Committed Pursuant to the Sexually Violent Predator Act?. (December 2016) - Azizian, Allen; Hutton, Shane; Hughes, Doriann; Sreenivasan, Shoba
Sexually Violent Predator statutes allow the involuntary treatment of individuals who are found to pose a threat to public safety. Most sex offender treatment programs rely on cognitive interventions to reduce the risk of recidivism. The purpose of this study was to examine (a) whether individuals with paraphilia diagnoses have cognitive deficits compared with the general population; (b) whether individuals diagnosed with pedophilia differed on cognitive performance when compared with individuals diagnosed with paraphilia not otherwise specified (NOS), nonconsent; and (c) whether individuals with paraphilia plus antisocial personality disorder (ASPD) differed in cognitive performance when compared with individuals with a paraphilia diagnosis only. The sample consisted of 170 males ( M age = 50.21; SD = 10.22) diagnosed with pedophilia or paraphilia NOS, nonconsent, who were detained or civilly committed to a forensic psychiatric hospital. Assessments included Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), Wechsler Abbreviated Scale of Intelligence (WASI), and Wide Range Achievement Test 4 (WRAT4). Individuals diagnosed with pedophilia and paraphilia NOS, nonconsent, obtained lower scores than matched controls based on the RBANS Immediate Memory, Visuospatial/Constructional, Delayed Memory indices and Total Score. In comparison with individuals with paraphilia NOS, nonconsent, those with pedophilia diagnosis had lower scores on the RBANS Delayed Memory. Individuals diagnosed with a paraphilia disorder combined with ASPD demonstrated trends toward lower IQ scores than those with a paraphilia diagnosis only. Treatment programs can improve their chance of success by assessment of cognitive processes, and offer therapy in a style that is consistent with the cognitive abilities of their clients.